Enhanced osteoconductivity of polyethersulphone nanofibres loaded with bioactive glass nanoparticles in in vitro and in vivo models. (29th June 2015) - Ardeshirylajimi, A.; Farhadian, S.; Jamshidi Adegani, F.; Mirzaei, S.; Soufi Zomorrod, M.; Langroudi, L.; Doostmohammadi, A.; Seyedjafari, E.; Soleimani, M.
Abstract Objectives There is growing need for new scaffold constructions for synthetic bone graft substitutes to repair large bone lesions. A very promising and important class of new implants for tissue engineering is based on three‐dimensional scaffolds and bioceramics. Materials and methods In this study, after investigation of mechanical properties of polyethersulphone (PES) nanofibres, fabricated by electrospinning methodology and coated with bioactive glass (BG), cells of the MG‐63 line were cultured on surfaces of these scaffolds. Their capacity to support MG‐63 proliferation was also investigated in vitro by MTT assay. Osteoconductivity on these scaffolds was investigated by the common osteogenic markers alkaline phosphatase (ALP) activity, calcium mineral deposition and bone‐related gene activation. Next, a bone reconstruction of rat critical‐size defects model was evaluated using radiographic imaging analysis (digital mammography), computed tomography and histological examination. Results In vitro results indicated that biocompatibility and osteogenic markers of MG‐63 cells were significantly enhanced after coating PES with BG. Based on in vivo results, new bone formation in the defect site was enhanced in implanted rats in comparison with a control group. The highest reconstruction was observed in animals implanted with BG‐coated nanofibres. Conclusions Osteoconductivity of PES nanofibres was markedly enhanced after coating them with BG, and introduction of this construct as new bone‐graft substitute for bone loss and defects is indicated.